2011
DOI: 10.1002/art.30366
|View full text |Cite
|
Sign up to set email alerts
|

CD4+CD28− T cell expansion in granulomatosis with polyangiitis (Wegener's) is driven by latent cytomegalovirus infection and is associated with an increased risk of infection and mortality

Abstract: Objective. Expanded populations of CD4؉ CD28؊ T cells with a cytotoxic phenotype have been repeatedly reported in patients with granulomatosis with polyangiitis (Wegener's) (GPA). In healthy individuals expansion of this T cell population follows cytomegalovirus (CMV) infection. We undertook this study to investigate whether CMV infection may be responsible for driving the expansion of CD4؉CD28؊ T cells in GPA patients and how this might relate to clinical features.Methods. Forty-eight GPA patients and 38 agem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 126 publications
(121 reference statements)
5
49
0
Order By: Relevance
“…Although sampling was not continued beyond the first year, the intensive protocol and detailed phenotyping conducted during this critical period add robustness and relevance to these findings, which are novel to transplantation but resonate with the inverse association between circulating CD4 + CD28 null cells and renal function in a cross-sectional study of stable patients with renal vasculitis (6). This link between CMV, inflammation (discussed earlier) cytotoxic CD4 + CD28 null cell expansion, endothelial injury, and allograft dysfunction may contribute to explaining the well-recognized but incompletely understood association between inflammation and graft outcome (30,31) and may even go toward explaining the "transplant paradox" by which improvements in acute rejection rates have not been mirrored by long-term improvement in graft survival (32).…”
Section: Increased Cd4mentioning
confidence: 81%
See 1 more Smart Citation
“…Although sampling was not continued beyond the first year, the intensive protocol and detailed phenotyping conducted during this critical period add robustness and relevance to these findings, which are novel to transplantation but resonate with the inverse association between circulating CD4 + CD28 null cells and renal function in a cross-sectional study of stable patients with renal vasculitis (6). This link between CMV, inflammation (discussed earlier) cytotoxic CD4 + CD28 null cell expansion, endothelial injury, and allograft dysfunction may contribute to explaining the well-recognized but incompletely understood association between inflammation and graft outcome (30,31) and may even go toward explaining the "transplant paradox" by which improvements in acute rejection rates have not been mirrored by long-term improvement in graft survival (32).…”
Section: Increased Cd4mentioning
confidence: 81%
“…CMV prophylaxis with 100 days of valganciclovir was given to the D+RÀ serostatus group only, with dose adjustment for renal function. Serial whole blood samples were taken for CMV DNA polymerase chain reaction in all patients at day 0 (before transplantation) and then at weeks 1,2,3,4,6,8,10,12,16,20,24,28,34,40,46, and 52. The clinical team remained unaware of these results, and no changes in clinical management ensued (it is not unit policy to undertake viral load testing and preemptive therapy in the context of asymptomatic CMV infection, as is the case in most centers, so these assessments were undertaken for research purposes only).…”
Section: Assessment Of CMV Serostatus Infection and Diseasementioning
confidence: 99%
“…6 The decreased lymphopoiesis and thymic involution also result in a reduction of naïve T cells and increasing frequency of memory T cells, 10,11 such as antigen-experienced memory T cells that respond to low-threshold stimuli and secrete cytotoxic factors, such as perforin and granzyme B (GrB). 12,13 For example, the elderly accumulate highly differentiated CD8 1 CD28 Low/-T cells 10,14 expressing GrB, 15 although a similar type of potentially cytotoxic cells are also induced after cytomegalovirus (CMV) and HIV infections (see Strioga et al 16 ); in some autoimmune diseases such as rheumatoid arthritis (RA), Graves disease, multiple sclerosis (MS), type 1 diabetes (T1D), and Wegener's granulomatosis [17][18][19] ; and in patients with inflammatory breast cancer after high-dose chemotherapy followed with autologous progenitor cell transplantation (auto-HSCT). 20 We recently found that antitumor effector GrB 1 CD8 1 T cells can also be induced when tumorsupporting regulatory B cells (Bregs) are rendered into activators expressing 4-1BBL.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Expansions of CD4 + CD28 − T-cells reported in RA and other autoimune diseases frequently exceed 5-10% (when not stratified by CMV infection status) and so vastly exceed the percentages observed in CMV − individuals where reported (about 1-2% in the literature). A small number of studies in RA and granulomatosis with polyangiitis (GPA) were actually stratified by CMV serology and found that the CD4 + CD28 − T-cell subset was increased by 10 to 20-fold in the CMV + population.…”
Section: Is This Simply a Coincidence?mentioning
confidence: 99%
“…A small number of studies in RA and granulomatosis with polyangiitis (GPA) were actually stratified by CMV serology and found that the CD4 + CD28 − T-cell subset was increased by 10 to 20-fold in the CMV + population. 4,6,7 It is becoming increasingly obvious that the expansions of CD4 + CD28 − T-cells observed in RA are explained by the CMV + population of RA patients; they may also explain the increased incidence of CV morbidity and mortality. This is, because, to make things worse, CMV infection in RA produces larger expansions of these cells than in otherwise healthy people, suggesting RA itself might accelerate these expansions.…”
Section: Is This Simply a Coincidence?mentioning
confidence: 99%